Integration and Disintegration in the Modern Global Economy - Bezrukova Nataliia V. (Bìznes Inform, 2017)
The article is aimed at studying the theoretical and practical aspects of the integration and disintegration processes in the global economy, evaluating their causes and consequences. The advantages and disadvantages of integration and disintegration processes have been researched. The main challenges facing the State in the process of integration have been outlined. The article particularly focuses on analyzing the causes for disintegration of countries. The features of disintegration processes are characterized on examples of individual integration groupings. The reasons for the integration of countries that lead to the creation of confined, competing economic blocs have been disclosed. On the basis of the carried out study has been concluded that the current world economy is constantly undergoing integration and disintegration processes. They require constant analyzing, as the formation of new associations requires critical evaluation of the experience of the preceding ones.